The Relationship Between Energy Consumption, Population and Economic Growth in Developing Countries - Mombekova, Gulmira; Nurgabylov, Murat; Baimbetova, Assel; Keneshbayev, Bektur; Izatullayeva, Bibigul (International Journal of Energy Economics and Policy, 2024)
The need for energy is increasing due to population growth and industrialization. The scarcity of energy resources on earth has pushed countries to research alternative energy sources and take new measures regarding energy. In the study, the relationship between variables was investigated using population, economic growth and energy consumption data of 7 countries in the developing countries category (China, India, South Africa, Indonesia, Turkey, Mexico, Thailand). The direction and magnitude of the impact of economic growth and population growth on energy consumption were examined using 1990-2022 data for 7 countries. The relationship between the variables was examined with Swamy's Random Coefficients Model and Seemingly Unrelated Regression (SUR) models, and the positive effect of economic growth on energy consumption was observed. The parameter of the economic growth variable varies between 0.49% and 0.81% for countries. However, it was concluded that the population variable had no effect on energy consumption in the 2 countries included in the analysis. The population variable is significant in explaining energy consumption at the 5% significance level for South Africa, Mexico and Thailand, and at the 10% significance level for Turkey and China, its statistically insignificant for India and Indonesia.